Entomopathogenic Nematodes for the Management of Plum Curculio in Highbush Blueberry - Ana Luiza Sousa; Cesar Rodriguez-Saona; Robert Holdcraft; Vera Kyryczenko-Roth; Albrecht M. Koppenhöfer (Biology, 2021)
Conotrachelus nenuphar Herbst (Coleoptera: Curculionidae) is a key pest of stone and pome fruits in the United States. Application of certain entomopathogenic nematode (EPN) species has shown efficacy in some crops when targeting the larval stage of C. nenuphar in soil. To date, however, no EPNs have been tested for the control of this pest in highbush blueberries. In 2020, laboratory and field studies were conducted to: (1) determine the persistence of Steinernema riobrave, S. carpocapsae, S. feltiae, and Heterorhabditis bacteriophora in acidic blueberry soil; (2) compare the virulence of these EPNs to C. nenuphar larvae and pupae; and (3) compare the efficacy of these EPN species to control this pest in blueberry fields. The greatest persistence in blueberry soil was exhibited by S. riobrave followed by S. carpocapsae. Superior virulence was observed in S. riobrave against C. nenuphar larvae and pupae. Promising levels of virulence were also observed in S. carpocapsae and S. feltiae against the larvae, but S. scarabaei had low virulence. In the field, S. riobrave provided significantly higher levels of C. nenuphar suppression (90%) than the other EPNs. The field efficacy of S. riobrave against C. nenuphar at low and high rates was confirmed in 2021. Steinernema riobrave has the potential to become an important component in the management of C. nenuphar in highbush blueberry.